(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Violence is clear in the story works of Zakarayya Tamer. It signifies most of his works forming a chracteristict that distinguishes his own works from other written works in this age and he proved himself a popular different writer who has his way stating with cursing and ending in crime regadless to his issues concerning (family, street,power) even if they are different if we think of circumastances which lead to this colour of writing. In this world the scenes of troublesome, fighting, raping and killing. Thus violence signifies this world in which it is difficult to live out of desire to blood by killing in the most terrified way seprating heads. This describes his way of revealing the disasterous sort of writing away from the causes of these problematic affairs which go deeper than what we are expecting. This is what the search is trying to deal with and focus.